2018
DOI: 10.1002/smj.2918
|View full text |Cite
|
Sign up to set email alerts
|

The power and limits of modularity: A replication and reconciliation

Abstract: Research Summary: We ask two questions: First, what are the underlying mechanisms that explain the power of modularity? Second, is the power of modularity robust in nonmodular problems? We replicate and then reconcile the key results in two prior models on modularity: E&L and S‐search. Our results yield several important insights. First, a significant portion of the advantage enjoyed by S‐search is attributed to multi‐bit mutation. Second, organization‐evaluation needs to be used in combination with multi‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Our finding highlights that the performance target plays an essential role in search, especially under imperfect evaluation. With these findings, this study bridges two core tenets of the behavioral theory of the firm: the tenet of the architecture on complexity (e.g., Simon 1962, Ethiraj and Levinthal, 2004, Fang and Kim, 2018 and the tenet of the performance target and aspiration level (e.g., Cyert andMarch, 1963, Greve, 2003).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our finding highlights that the performance target plays an essential role in search, especially under imperfect evaluation. With these findings, this study bridges two core tenets of the behavioral theory of the firm: the tenet of the architecture on complexity (e.g., Simon 1962, Ethiraj and Levinthal, 2004, Fang and Kim, 2018 and the tenet of the performance target and aspiration level (e.g., Cyert andMarch, 1963, Greve, 2003).…”
Section: Discussionmentioning
confidence: 61%
“…Subsequent theoretical studies have shown that decomposability helps firms discover a promising option by facilitating module-level experimentations (i.e., producing more variations) (Kogut and Bowman, 1995, Baldwin and Clark, 2000, Marengo, Dosi, Legrenzi, & Pasquali, 2000, Ethiraj and Levinthal, 2004, Fang and Kim, 2018. As Knudsen and Levinthal (2007) note, a critical facet has been largely underexplored in this tradition, namely, how firms select and retain the promising ones among experimented options.…”
mentioning
confidence: 99%
“…The NK model describes the rugged fitness landscape of complex problems, where the peaks represent alternative solutions generated by decision sets (N) and their interdependencies (K) (Levinthal, 1997;Caner et al, 2017;Fang and Kim, 2018). According to the NK model, new product development comprises complex problems that cause high task uncertainties with high information processing requirements (Tushman and Nadler, 1978;Fleming and Sorenson, 2001;Ethiraj and Levinthal, 2004;Baumann et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Hierarchy and decomposability, in turn, are key drivers for the efficacy of search (Ethiraj and Levinthal 2004a, c;Simon 1962). Interestingly, while prior research has emphasized the importance of near decomposability (Fang and Ji-hyun 2018;Simon 2002), research on hierarchy has not similarly examined the effects of different "degrees of hierarchy". This is the more surprising given that most organizations in real world contexts are only nearly hierarchical rather than fully hierarchical (see, Rivkin and Siggelkow (2002) or Black et al (1999) for examples).…”
Section: Core Periphery and Changementioning
confidence: 99%